Electronically tunable current-mode universal biquad filter based on the CCCCTA - Singh V.S.; Mohan J.; Maheshwari S.; Chauhan D.S. (My University, 2025)
This paper presents an electronically tunable current-mode universal biquad filter based on the current controlled current conveyor transconductance amplifiers (CCCCTAs). The proposed filter employs only three CCCCTAs , two capacitors one of which is permanently grounded. The proposed filter realizes low pass (LP), band pass (BP) and high pass (HP) responses simultaneously. The filter can also realize regular notch and all pass(AP) responses with interconnection of relevant output currents .The low pass notch (LPN) and high pass notch (HPN) responses can also be realize without passive component matching conditions. The circuit enjoys an independent current control of pole frequency and bandwidth .Both the active and passive sensitivities are no more than unity. The validity of proposed filter is verified through PSPICE simulations. © 2009 IEEE.